Variáveis de controle do comportamento governado por regras: uma análise de métodos e resultados de estudos da área - TEIXEIRA JÚNIOR, Ronaldo Rodrigues (Universidade Federal do Pará, 2011)
Some authors have suggested that rules can produce insensibility of behavior to programmed reinforcement contingencies. Others, however, have suggested that this insensibility tend to occur, not due to inherent properties of rules, but due to the type of reinforcement schedule used in the studies. One problem, nevertheless, is that there are experimental evidences showing that the behavior of following rules different from programmed contingencies can be either maintained or interrupted, independently if the reiforcement schedule is intermittent or continuous. It is possible that such results differences occurs due differences in methods of the studies that have been producing this results, but this is not sufficiently explained in literature. The present work had as objective join and compare the main studies that investigated rule control in different schedules of reinforcement, with purpose to investigate if specific features of the methods used in these studies could contribute, or not, to the occurrence of differences in the results. For this, it was adopted the following procedure: 1) selection of the main experimental papers in the area that investigated the role of different types of reinforcement schedules in sensibility of rule following to contingencies; 2) sort out the texts in groups according to the method used for each research group; 3) analysis of methods and results of studies of the same group or in comparison with studies of other groups; 4) discussion of results based on the explanations that the authors give to their results and in relation of results of other studies not considered by the authors. The main results were as follow: in all of the 5 groups occurred sensitive and insensitive performance among subjects, not depending at least exclusively of the type of schedule that was been used; in 3 of 5 groups there was a persistency of insensitive results among subject, while in 2 of 5 groups there was a persistency of sensitive results; the differences in results of sensibility and insensibility in each group seems to have depended up on some variations in the methods that were used and not only from the type of schedule of reinforcement. Some of these variations in methods have not been sufficiently studied in the area and can be interfering with the results. Some examples that were discussed would be: the control of instructions contents, the way of delivering reinforcers, the features in selecting subjects and the difficulty level of task used. Studies that had as specific objective manipulate these variables with the purpose of better control their effects could guarantee a better efficiency of methods used to study rule control. These new investigations could help developing minimal controlling parameters for the realization of new studies.